Socio-economic inequalities in smoking prevalence and involuntary exposure to tobacco smoke in Argentina: Analysis of three cross-sectional nationally representative surveys in 2005, 2009 and 2013 - Hernández Vásquez, Akram (2019)
Background Understanding patterns of socio-economic inequalities in tobacco consumption is key to design targeted public health policies for tobacco control. This study examines socio-economic inequalities in smoking and involuntary exposure to tobacco smoke between 2005 and 2013. Methods Data were derived from the Argentine National Risk Factors Surveys, conducted in 2005, 2009, and 2013. Two inequality measures were calculated: the age-adjusted prevalence ratio (PR) and the disparity index (DI). Educational level, household income per consumer unit and employment status were used as proxies for socio-economic status (SES). Generalized linear models were used in the analysis. Results Prevalence of smoking decreased from 29.7% to 25.1% between 2005 and 2013, mainly in women (p<0.001). Despite the overall prevalence reduction, socio-economic inequalities in smoking persisted. For both men and women, the DI was moderately high for smoking (14.47%-33.06%) across the three surveys. In men, the PR indicated a higher smoking prevalence for lower educational levels and lower household income throughout the analyzed period. In women, unlike previous years, the 2013 survey showed disparity related to unemployment. Involuntary exposure to tobacco smoke in 2013 was associated with educational level and household income, with lower involuntary exposure among those with higher SES. Conclusions While overall smoking rates have decreased in Argentina, socio-economic disparities related to tobacco smoking persist. Comprehensive tobacco control programs targeted to address these inequalities are essential in developing strategies to reduce health disparities in tobacco-related diseases.